The Effectiveness of the Blackboard Technique in Integrating Saudi University ‎Students’ English-Language Reading and Writing Skills‎ - Nasr, Mahmoud (Jordan Journal of Educational Sciences, 2021)
The aim of the current study was to test the effectiveness of the Blackboard technique in integrating English-language reading and writing skills of Saudi university students. The participants of the study consisted of 40 students selected randomly from Qassim University, including both males and females. The one-group experimental design was used. After pretesting, the experimental-group students were taught by using a proposed model implementing a suggested Blackboard-based strategy. The strategy aimed at integrating reading and writing. Then, the posttest was administered. Results indicated that there were statistically significant differences between the mean scores of the students in the pre -and post- administrations of the test in favor of the post-administration. No significant differences were detected between the mean scores of males and females in the experimental group in the post administration of the test